Basilar artery aneurysm associated with Behcet's disease - Aktas, Ebru Gercek; Kaplan, Metin; Ozveren, Mehmet Faik (Turkish Neurosurgical Soc, 2008)
Vascular involvement is common in Behcet's Disease (BD). The venous system is often affected, while arterial system involvement is a rare occurrence. Intracranial aneurysm formation associated with BD is extremely rare. A 38-year-old male patient with BD under the follow-up of the Dermatology department presented with acute headache. The cranial computed tomography revealed subarachnoid bleeding. A basilar artery aneurysm, which was ruptured during the procedure, was found on the cerebral angiography and the patient died the next day. This report adds our case to the literature of posterior cerebral circulation aneurysms associated with BD among the limited number of articles on this topic.
Keywords: basilar artery; aneurysm; Behcet's disease